2018
DOI: 10.15405/epsbs.2018.02.19
|View full text |Cite
|
Sign up to set email alerts
|

Migration: From Social Inclusion To Successful Integration

Abstract: This article discusses the theoretical concepts of social inclusion and integration, topic, which have received new attention with the recent rise in international migration. According to the UN, "Social inclusion and integration are a key goal for social development", and a clearer understanding of these concepts can contribute to building better migrant programs. Here the authors develop a theoretical model based on empirical research conducting in Norway that reflects the relationship between social inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Besides, it was revealed that immigrants, living in Canada, who have chosen integration setting, least of all suffered from acculturation stress. At the same time those, who have chosen marginalization, most of all suffer from acculturation stress; those, who have chosen separation, suffer from acculturation stress less than those, who have chosen marginalization, but more than those, who have chosen integration [4], and as the result successefull integration [12]. The results of ICSEY cross-cultural survey, participants of which were teenage immigrants from 13 countries and four continents [5], confirmed these data.…”
Section: Materials and Modelssupporting
confidence: 52%
“…Besides, it was revealed that immigrants, living in Canada, who have chosen integration setting, least of all suffered from acculturation stress. At the same time those, who have chosen marginalization, most of all suffer from acculturation stress; those, who have chosen separation, suffer from acculturation stress less than those, who have chosen marginalization, but more than those, who have chosen integration [4], and as the result successefull integration [12]. The results of ICSEY cross-cultural survey, participants of which were teenage immigrants from 13 countries and four continents [5], confirmed these data.…”
Section: Materials and Modelssupporting
confidence: 52%